Analisis Sistem Penyimpanan Bahan Kering Berdasarkan Food Code 2022 di Dry Storage PT ABC - Kayla Febrianti; Niken Purwidiani; Ila Huda P Dewi; Aisyah Nurin Kamiliya (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the dry material storage system based on the 2022 Food Code at PT ABC Dry Storage and identify factors that need to be considered in the storage of dry materials. This study uses a qualitative descriptive method. Data collection was carried out through observation, interviews, and documentation. The research informants consisted of warehouse managers, warehouse coordinators, and dry storage staff who were selected purposively based on direct involvement in dry material storage activities. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the dry material storage system at PT ABC's Dry Storage has implemented several principles in accordance with the 2022 Food Code, including the use of shelves and pallets to prevent direct contact of materials with the floor, the application of FIFO (First In First Out) and FEFO (First Expired First Out) methods), material labeling, separation of materials by type, as well as regular implementation of hygiene and pest control programs. However, there are still several aspects that require attention, especially related to the control of the temperature and humidity of the storage room to comply with the recommended standards. Factors to consider in a dry materials storage system include material moisture content, storage temperature, air relative humidity, presence of microorganisms, and warehouse pests. The control of these factors plays an important role in maintaining the quality, safety, and shelf life of dry foodstuffs. This research is expected to be an evaluation and reference material in an effort to improve the dry matter storage system in accordance with the principles of food safety.